Integrated transcriptomics and machine learning reveal REN as a dual regulator of tumor stemness and NK cell evasion in Wilms tumor progression - Cao, Qingfei; Li, Junyi; Zou, Yunfei; Xu, Changwen; Tang, Huihui; Chen, Meixue (Frontiers in Immunology, 2025)
IntroductionWilms tumor (WT) is the most common pediatric kidney cancer, which presents significant therapeutic challenges, particularly in high-risk cases, due to chemotherapy resistance and immunosuppressive tumor microenvironments (TMEs). Tumor stemness and immune evasion mechanisms are implicated in poor clinical outcomes, yet the molecular drivers underpinning these processes remain inadequately understood.MethodsWe employed an integrative approach combining single-cell RNA sequencing (scRNA-seq), spatial transcriptomics, bulk RNA-seq, and advanced machine learning techniques to uncover molecular regulators of tumor behavior in WT. A novel Cancer Stemness Prognostic Index (CSPI) was developed using machine learning algorithms to stratify WT patients by risk and histological subtype. Additionally, molecular docking simulations and in vitro functional assays were performed to validate the role of key regulators in tumor stemness and immune evasion, as well as to explore potential therapeutic strategies targeting these molecular drivers.ResultsRenin gene (REN) emerged as a central regulator of tumor stemness and immune evasion in WT. High-CSPI tumors exhibited enhanced tumor stemness phenotypes, metabolic reprogramming (ROS/oxidative phosphorylation), and suppressed immune activity. Spatial transcriptomics revealed distinct histological subtype-specific localization of stemness-related gene expression and physical proximity between REN-expressing tumor cells and natural killer (NK) cells. At spatial and single-cell resolution, REN-expressing tumor cells promoted NK cell exhaustion via PTN-NCL and COL4A1-CD44 ligand-receptor interactions, while showing limited impact on T cell dysfunction. Molecular docking identified estrogen-based compounds as potential REN inhibitors. Functional assays validated REN knockdown as significantly impairing tumor proliferation, migration, and survival in vitro.DiscussionThis study establishes REN as a pivotal driver of tumor stemness and immune evasion in WT, playing a dual role in promoting tumor aggressiveness and suppressing NK-mediated immune surveillance. Targeting REN offers promising therapeutic opportunities for high-risk WT cases by simultaneously inhibiting tumor progression and restoring immune function. These findings emphasize REN’s potential as a transformative target for precision oncology and underscore the value of integrative transcriptomics in advancing personalized cancer treatment strategies.